The time interval between the hCG trigger and the oocyte pickup on IVF outcomes in patients with decreased ovarian reserve and poor prognosis - Özer, Gönül; Balın Düzgüner, İpek Nur and Özmen, Sevinç and Kahraman, Semra (The European Research Journal, 2025)
Objectives: This study aimed to evaluate the effect of varying intervals between human chorionic gonadotropin (hCG) administration and oocyte pickup (OPU) at 34, 35, and 36 hours on in vitro fertilization (IVF) outcomes and embryo development in patients with diminished ovarian reserve (DOR). Methods: This retrospective cohort study utilised the Istanbul Memorial Şişli Hospital, assisted reproductive technology (ART) and Reproductive Genetics Center databases from January 2017 to March 2024. The study included women undergoing ART cycles with DOR, as defined by the Bologna criteria, and follicle-stimulating hormone (FSH) levels exceeding 12 IU/L on day 2 of menstruation. Nine hundred and forty-nine ovarian stimulation cycles were analysed using the gonadotropin-releasing hormone antagonist protocol and triggered by recombinant hCG (r-hCG). The cycles were divided into three groups based on the time interval between r-hCG injection and OPU at 34, 35, and 36 hours. Demographic characteristics, ovarian stimulation parameters, embryological outcomes, and pregnancy results were compared across these groups. Results: The 36-hour OPU group demonstrated the highest fertilization, best embryological outcomes, including the highest blastocyst formation rate (14.95%) compared to the 34-hour (14.23%) and 35-hour (12.43%) groups (P=0.025). The 36-hour group also had the highest proportion of day 5–6 embryo transfers (33.8%, P=0.001). However, there were no significant differences in pregnancy outcomes. Conclusions: In DOR patients, extending the OPU interval to 36 hours with hCG triggering showed higher fertilization rates and better embryo development than 34 and 35 hours. However, it did not affect pregnancy outcomes.